Ethics for Radiation Protection in Medicine - Malone, Jim (Series in Medical Physics and Biomedical Engineering, 2019)
This book presents an up to date ethical framework for radiological protection in medicine. It is consistent with the requirements of the system of radiation protection and with the expectations of medical ethics. It presents an approach rooted in the medical tradition, and alert to contemporary social expectations. It provides readers with a practical framework against which they can assess the safety and acceptability of medical procedures, including patients' concerns. It will be an invaluable reference for radiologists, radiation oncologists, regulators, medical physicists, technologists, other practitioners, as well as academics, researchers and students of radiation protection in medicine. Features: An authoritative and accessible guide, authored by a team who have contributed to defining the area internationally Includes numerous practical examples/clinical scenarios that illustrate the approach, presenting a pragmatic approach, rather than dwelling on philosophical theories Informed by the latest developments in the thinking of international organizations